Investigating Problems Encountered By The Test Takers During Taking Toefl Test - Rahman, Arif; Purwaningtyas, Maya (Lembaga Penelitian dan Pendidikan Mandala, 2023)
One of standardized test that measure students’ proficiency level in English which is called as Test of English as Foreign Language (TOEFL) has been used worldwide by more than 9.000 colleges, universities and agencies in more than hundreds countries in the world. Nowadays, English proficiency test is taken not only on purpose of pursuing study abroad but also as a prerequisite to complete college, especially in institutions. Further, it is also used in the admissions process of applicants to get a job especially in companies where English is used to communicate. However, to pass the TOFL test is not an easy task and even there are many test taker failed the test though they had spent months preparing for the test. There are many problem happened during the test that caused the test taker into failure. This research aimed to investigate problems that occur during the test. This study used descriptive qualitative design and the subjects were ten college students who had taken TOEFL prediction test in the Language Center of Mandalika University of Education (UNDIKMA). The instrument used in this study was an interview which then the result of interview was analyzed in three steps, i.e. data condensation, display, and conclusion. The result of the study showed that most of the test taker failed and made a bad score due to some problems, i.e. less practice, lack of vocabulary, bad time management, feeling nervous, etc. It was noted that those who had minimum problem scored higher than those who had various problem.